O "forró dos velhos" e as reconfigurações do lazer em tempos de pandemia: um estudo sobre o gênero, velhice e sociabilidade - Monteiro, Yohana Tôrres (2021)
The sociological problem to be investigated is the experience in times of pandemic of older women participating in the “forró dos Velhos” in Cascavel/CE, whose cut was a group of women aged between 71 and 79 years old, who attend this forró. The analytical hypotheses are: First, that there has been a change in the way of life of older women in contemporary times and, second, that women are having more freedom in their aging process in the 21st century. In the theoretical framework we will have authors such as Beauvoir (1990); Butler (2012); Camarano (2012); Debert (1999); Menezes (2012); Mesquita (2014); Motta (1999); Rocha (2015); among others. This dissertation lists three categories of analysis: “old age”, “gender” and “sociability” which will be analyzed through the “forró dos Velhos” in Cascavel, Ceará. The research in question took place between January 2020 and July 2021. The methodology was qualitative. The technique chosen for data collection was a semi-structured interview through phone calls via whatsapp, face-to-face meetings and field observation. Data collection revealed how forró for Majors is important for the socialization of these women and how the pandemic had a great impact on their lives, affecting the daily lives of these women. The main finding was that female aging in the 21st century is unfolding in a new way, that is, these women claim autonomy and freedom in their biographical paths, a demand never imagined before. In this sense, this work questioned the social roles historically assigned to them and theirs, supposedly in the private sphere. They are women from the popular classes, with low education and use this space in the city as one of the only possible forms of leisure, and there they break taboos and values, which seemed to be crystallized in their daily lives. The research also describes the experiences of reconfiguration of leisure that the subjects are facing during this period of COVID-19.